Desire for the political in the aftermath of the Cold War - Dzenovska, D; De Genova, N (Berghahn Journals, 2018)
In this introduction, we reflect on the proliferation of an amorphous desire for the political in the post–Cold War era. The desire for the political, we argue, is shaped by two sets of tensions: the desire to criticize power via forms of action conventionally characterized as “politics,” but without a clear analysis of how power is organized or exercised; and the desire to overcome the present in the name of an alternative (better) future, but without a clear sense of the form that future might take. We start from the vantage points of critical scholarship that distinguishes itself from the mainstream, and people and places that are geopolitically in Europe, but “not quite” European if viewed in relation to “Europe” as a normative trope.